Analisis Konsep Hospital Without Walls pada Pelayanan Kelainan Refraksi di UPTD Rumah Sakit Mata Provinsi Sulawesi Utara - Gabriella O. Mokolensang; Aaltje E. Manampiring; Jimmy Posangi (Medical Scope Journal, 2024)
A hospital without walls or known as a hospital without walls is very useful for patients who come to the hospital for treatment with referrals from the public health center as the entry point for referral diagnosis, this is to minimize the risk of infection transmission and other disease problems. The purpose of this study is to analyze the concept of a hospital without walls and the obstacles and challenges in providing refractive errors. The research was conducted at the UPTD Eye Hospital in North Sulawesi Province, from January to December 2022 using in-depth interviews with five research informants, namely the director, head of medical services, ophthalmologist, family doctor and patient. Instruments in the form of in-depth interview guidelines and a list of questions that have been provided. The stages of data processing are narrating, inferring, reducing, recording, sampling, unitizing. Data analysis is content analysis. The validity of the research results using triangulation of data sources and methods. The results of this study were obtained from the summary of the answers of the research informants that the concept of a hospital without walls all understand and know this concept to mitigate the accumulation of services in hospitals, but this concept has not been implemented because there are several factors such as standard operating procedures, human resources and infrastructure which is not yet possible for some FKTPs to be able to complete services at the community health center or family doctor, the obstacle presented by the informant is that there are still many patients who want to carry out direct services to the hospital without going to the health center or family doctor, another obstacle is the lack of tools for examining refractive errors and competence general practitioners to be able to make referrals in the diagnosis of disease. Hospital income will also increase if implementing this concept, if there is collaboration with related stakeholders such as BPJS Health, the Health Service, and other private parties, so that this will also have a good impact on the quality of service when hospital accreditation is carried out. The sophistication of information technology needs to be implemented as much as possible from the hospital so that it is easier so that patients do not pile up during services by registering online. The conclusion of this study is that the concept of a hospital without walls has not been implemented in the Eye Hospital of North Sulawesi Province because it has not followed standard operating procedures, quality competent resources and adequate infrastructure. FKTP Puskesmas in providing refractive error services have not provided complete supporting tools and the skills of FKTP doctors are still lacking, this will have an impact on assessing hospital accreditation in the quality of health services. Keywords: hospitals without walls, eye refractive error, family doctors